A new sexually dimorphic Hyphessobrycon from the western Amazon basin (Characiformes: Characidae) - Lima, Flávio C.t.; Bastos, Douglas A.; Py-Daniel, Lúcia H. Rapp; Ota, Rafaela P. (Zootaxa, 2022)
A new species of Hyphessobrycon presenting dimorphic males is described from the western Amazon basin in Brazil, Colombia, Ecuador, and Peru. The new species has been mistakenly identified in the literature with the non-congener Hemigrammus marginatus, with which shares a similar color pattern by presenting dark patches of dark pigmentation on caudal-fin lobes. It can be distinguished from the latter species, as well as from Hemigrammus durbinae, and two similar congeners, Hyphessobrycon diancistrus and Hy. otrynus, all of which sharing the same caudal fin color pattern, by the combination of presenting a dark patch of pigmentation on the dorsal fin, a single large anal-fin hook at the last unbranched anal-fin ray in mature males, and a moderately high body depth (22.4–32.5 % SL, mean 28.4 %). The new species is more similar to Hyphessobrycon diancistrus, which is putatively its closely related taxon. A putative close relationship with Hyphessobrycon otrynus, and with a non-congener presenting a distinct color pattern but sharing a similar sexual dimorphism on anal-fin hook morphology, Hemigrammus boesemani, is suggested.